2021
DOI: 10.1017/s0022226720000535
|View full text |Cite
|
Sign up to set email alerts
|

Explaining grammatical coding asymmetries: Form–frequency correspondences and predictability

Abstract: This paper claims that a wide variety of grammatical coding asymmetries can be explained as adaptations to the language users’ needs, in terms of frequency of use, predictability and coding efficiency. I claim that all grammatical oppositions involving a minimal meaning difference and a significant frequency difference are reflected in a universal coding asymmetry, i.e. a cross-linguistic pattern in which the less frequent member of the opposition gets special coding, unless the coding is uniformly explicit or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 55 publications
2
48
0
3
Order By: Relevance
“…The length of referential expressions is known to depend on their accessibility ( Ariel, 1990 ), which is determined by common ground ( Clark and Wilkes-Gibbs, 1986 ). As for morphosyntactic coding asymmetries and splits, it is well known that more predictable grammatical meanings are expressed by shorter forms (including zero) than less predictable ones (e.g., Jäger, 2007 ; Kurumada and Jaeger, 2015 ; Kurumada and Grimm, 2019 ; Haspelmath, 2021 ). Lemke et al (2021) demonstrate that fragments (i.e., incomplete sentential structures) encoding events known from everyday scripts and scenarios are perceived as more natural than fragments encoding unpredictable events.…”
Section: Some Problems With Efficient Trade-offsmentioning
confidence: 99%
“…The length of referential expressions is known to depend on their accessibility ( Ariel, 1990 ), which is determined by common ground ( Clark and Wilkes-Gibbs, 1986 ). As for morphosyntactic coding asymmetries and splits, it is well known that more predictable grammatical meanings are expressed by shorter forms (including zero) than less predictable ones (e.g., Jäger, 2007 ; Kurumada and Jaeger, 2015 ; Kurumada and Grimm, 2019 ; Haspelmath, 2021 ). Lemke et al (2021) demonstrate that fragments (i.e., incomplete sentential structures) encoding events known from everyday scripts and scenarios are perceived as more natural than fragments encoding unpredictable events.…”
Section: Some Problems With Efficient Trade-offsmentioning
confidence: 99%
“…It is often claimed that discourse frequency determines rather than correlates with other properties of functional and formal markedness (cf. Greenberg 1966: 65-69;Croft 2003;Haspelmath 2006Haspelmath , 2020a. This paper showed that A-prominent constructions both increased in discourse frequency and acquired properties associated with prototypical semantic and discourse transitivity in more innovative varieties.…”
Section: Discussionmentioning
confidence: 81%
“…formally marked (see §4.2), we suggest that functional properties may in fact drive the alignment shift, in line with similar claims about the role of frequency and functional pressures in the typological literature (cf. DuBois 1985: 363;Johns 1999: 79;Croft 2003: 117;Hawkins 2004;Haspelmath 2020aHaspelmath , 2020b.…”
Section: Functional Markedness and Alignment Shiftmentioning
confidence: 99%
“…The former relates to ease of learning; while the latter relates to low information loss or communicative cost (the terminology and foci vary between authors and disciplines, cf. Beckner, Pierrehumbert, & Hay, 2006; Bentz, Alikaniotis, Cysouw, & Ferrer‐i Cancho, 2017; Carr et al., 2020; Carstensen, Xu, Smith, & Regier, 2015; Denić, Steinert‐Threlkeld, & Szymanik, 2021; Fedzechkina et al., 2012; Gasser, 2004; Haspelmath, 2021; Kemp & Regier, 2012; Kirby & Hurford, 2002; Kirby et al., 2015; Nölle et al., 2018; Smith, 2020; Steinert‐Threlkeld & Szymanik, 2020; Uegaki (in preparation); Winters et al., 2015; Zaslavsky, Regier, Tishby, & Kemp, 2019b). Thesestudies have yielded converging evidence that languages which are learned and used in communication—the real‐world ones, the artificial ones grown in the lab, as well as those evolved by computational agents—all aspire to balance these two pressures, ending up somewhere along the optimal frontier.…”
Section: Discussionmentioning
confidence: 99%